Hypercoagulable states in young adults with ischemic stroke in a Stroke Belt state: a retrospective study - David Lee Gordon; Sarah R. Durica (Frontiers in Neurology)
We theorize that the southeastern United States has a higher stroke mortality rate and higher recurrent ischemic stroke rate than the rest of the United States due to (1) an increased prevalence of hypercoagulable states among young adults in the region, (2) failure to diagnose hypercoagulable states as the cause of ischemic stroke in young adults, and (3) underutilization of anticoagulation for ischemic stroke secondary prevention in young adults with hypercoagulable states. In an attempt to investigate this hypothesis, we conducted a retrospective chart review of 311 inpatients with first-ever ischemic stroke from age 18 to 55 years at an Oklahoma academic medical center from 1 July 2011 to 30 April 2017. Using Chi-squared test, we compared the stroke etiologic diagnosis of the attending neurologist at discharge—when hypercoagulable profile results were rarely available—to the diagnosis of a vascular neurologist postdischarge who had access to all available etiologic test results. The inpatient neurologists identified the stroke etiology as hypercoagulable state in 79 patients (25.57%) and undetermined etiology in 105 (33.98%). With the benefit of final hypercoagulable profile results, the postdischarge vascular neurologist identified the stroke etiology as hypercoagulable state in 167 (54.22%, 95% CI 48.64–59.70%, p-value <2.2e-16) and undetermined etiology in 28 (9.09%, 95% CI 6.36–12.83%, p-value 1.03e-14). There was no significant change in the proportion of ischemic strokes classified under all other stroke etiologies. We conclude that hypercoagulable states are a common and underrecognized cause of ischemic stroke in young adults in the U.S. Stroke Belt.